The American presence in Ulster : a diplomatic history, 1796-1996 - Carroll, Francis M. (Catholic University of America Press, 2005)
This book tells the story of the link between Ulster and the United States and presents the first general history of the U.S. Consulate in Belfast. While many historians have written about the impact of Ulster on the United States, this book also highlights the profound impact the United States has had on Ulster. The history of the Consulate General provides a unifying theme in this story, and the rich resources of the U.S. State Department and the Public Records Office of Northern Ireland make possible a unique view of both the culture and commerce of the province and also the growth of the Consular Service. --from publisher description.